Verbal and visual learning ability in patients with treatment-resistant schizophrenia: A 1-year follow-up study - Urska Arnautovska; Kathryn Vitangcol; James P. Kesby; Nicola Warren; Susan L. Rossell; Erica Neill; Anthony Harris; Cherrie Galletly; David Castle; Dan Siskind (Schizophrenia Research: Cognition, 2023)
Objective: In the general population, repeated cognitive testing produces learning effects with potential for improved test performance. It is currently unclear whether the same effect of repeated cognitive testing on cognition pertains to people living with schizophrenia, a condition often associated with significant cognitive impairments. This study aims to evaluate learning ability in people with schizophrenia and—considering the evidence that antipsychotic medication can additionally impair cognitive performance—explore the potential impact of anticholinergic burden on verbal and visual learning. Method: The study included 86 patients with schizophrenia, treated with clozapine, who had persisting negative symptoms. They were assessed at baseline, weeks 8, 24 and 52 using Positive and Negative Syndrome Scale, Hopkins Verbal Learning Test–Revised (HVLT-R) and Brief Visuospatial Memory Test-R (BVMT-R). Results: There were no significant improvements in verbal or visual learning across all measurements. Neither the clozapine/norclozapine ratio nor anticholinergic cognitive burden significantly predicted participants' total learning. Premorbid IQ was significantly associated with verbal learning on the HVLT-R. Conclusions: These findings advance our understanding of cognitive performance in people with schizophrenia and demonstrate limited learning performance in individuals with treatment-refractory schizophrenia.